Communication competences of multiple sclerosis neurologists during advance care planning conversations: A multi-observer study - Andrea Giordano; Ludovica De Panfilis; Roberta Martina Zagarella; Giulia Di Domenico; Mariangela Farinotti; Alberto Gajofatto; Maria Grazia Grasso; Alessandra Lugaresi; Sara Montepietra; Francesco Patti; Claudio Solaro; Riccardo Orlandi; et al. (PLoS ONE, 2026)
Background The ConCure-SM intervention [ISRCTN48527663] consists of an advance care planning (ACP) training program for neurologists/other professionals caring for people with progressive multiple sclerosis (PwPMS). We assessed the communication competences of ACP-trained neurologists who participated in the trial. Methods Eighteen ACP conversations were audio-recorded. After each conversation, participants (PwPMS, significant others [SOs], and neurologists) rated the neurologist’s communication skills using dedicated versions of the Quality of Communication questionnaire (QOC). Independent observers assessed the conversations using the Observing Patient Involvement in Shared Decision Making (SDM; OPTION), and the Verona Coding Definitions of Emotional Sequences (VR-CoDES). Results Mean duration of the ACP conversations was 62.7 minutes. Neurologists (5/7 women) were 30–62-year-old. PwPMS mean age was 61.8 years, 39% were women. Mean QOC scores (distinguished in general communication and end-of-life communication; 0–100 scale) were 92.4, 90.1 respectively, according to PwPMS; 95.2, 94.3 according to SOs. Mean neurologists’ self-reported QOC score (0–100 scale) was 69.5. Mean OPTION score (0–100 scale) was 48.4. PwPMS expressed a median of 8.5 cues (hints to emotion) and 3.0 concerns (explicit expressions of emotion) per conversation. Neurologists provided space to 59% of cues and 73% of concerns. A quarter of cues/concerns contained figurative expressions or metaphors to express concerns or as signals of emotional distress. Moreover, 12% of expressions were coded as positive emotional statements (i.e., expressions indicating hope, confidence, and positive wishes). Conclusions Neurologists’ communication skills during ACP conversations were rated as high using the QOC by both PwPMS and SOs, while neurologists rated their own skills more critically. Neurologists’ SDM competences were moderate, but higher compared to two published studies on MS consultations. Qualitative and quantitative analysis of ACP conversation transcripts indicate that ACP can evoke many emotions. In most instances neurologists provided space for the PwPMS to elaborate on affective expressions. Trial registration ISRCTN48527663.